MANAJAMEN SARANA DAN PRASARANA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Dea Nurshadrina Sausan; Naya Aulia Kamil; Zulfa Amalia Hasyim; Arita Marini (Bajang Institute, 2024)
Education is used as a basis for human action, this makes everyone entitled to education. According to Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System, it is explained that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength. , self-control, personality, intelligence, noble character, and skills needed by himself, society, nation and state. Facilities and infrastructure management can be defined as a collaborative process of utilizing all educationalManagement of educational facilities and infrastructure is tasked with arranging educational facilities and infrastructure so that they can contribute optimally and meaningfully to the course of the educational process. Facilities and infrastructure play an important role in the continuity of learning activities in schools. Having adequate facilities and infrastructure will certainly increase the comfort and success of student learning outcomes at school.